First Attempt Intubation Success Rate with Video Laryngoscope after Failed Direct Laryngoscopy - Shoaib Malik, Shahneela Raza, Muhammad Nadeem Muneer, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Several unsuccessful intubation attempts prompted the authors of this study to investigate the efficacy of the C-MAC video laryngoscope. Methods: After first attempts with a Macintosh direct laryngoscope were unsuccessful, patients were ultimately able to be intubated with the help of C-MAC laryngoscopes. It was determined whether or not there was a correlation between the positive outcome of C-MAC catheterization and the laryngeal photographs that were produced by the device. Study design: Descriptive Cross sectional Study Settings:Department of Anesthesia, Jinnah Postgraduate Medical Centre Karachi Study duration:January 2021 to January 2022 Results: Cormack and Lehane gave the Macintosh laryngoscope ratings of III and IV, however CMAC gave scores of I to 13 patients, II to 7 patients, and III to one patient. Tracheal intubation with CMAC was successful in 16 patients (76.2% percent) on the first try, and in 5 patients on the second attempt (23.8% percent). Only a trace of blood was discovered on the blades of three patients (14 percent). Conclusion: During routine anaesthetic treatment, a C-MAC video laryngoscope can successfully overcome unsuccessful intubations. The C-MAC video laryngoscope is a key recovery instrument that is both efficient and safe in the case of an intubation failure.